Surveying all public drinking water fountains in a city: outdoor field observations and Google Street View - Nick Wilson; Louise Signal; George Thomson (Elsevier, 2018)
Abstract Objective: Drinking fountains are a public amenity that may help counter the obesogenic environment (sugary beverages) and reduce the risk of heat stroke during heat waves. As a case study, we aimed to survey all public fountains in a city: Wellington, New Zealand, and to determine the utility of Google Street View in studying drinking fountains. Methods: Using a sample of all public drinking fountains in a City Council map, a field observer assessed their exact location and tap functionality, and photographed them. Google Street View was also used by the field observer and an independent observer to attempt fountain detection. Results: There were 47 fountains, found in only 6% of children's playgrounds and 29% of the parks (for a sample of the 10 largest suburbs). While the field observations showed that all 74 taps at the fountains delivered water, only 47% had taps for easy filling of drinking water bottles, and only 15% had bowls for dogs to drink from. Visible discolouration from algae/metal degradation was adjacent to 47% of nozzles. Google Street View detection of fountains by the field observer was successful for 68% and for 52% by the independent observer. Conclusions: The fountains were of generally high quality, but discolouration around the nozzle was common. Implications for public health: Additional investment in public fountains may be needed.